TRANSITIVITY ANALYSIS OF GRADUATE STUDENTS’ CASUAL CONVERSATION - Anjar Setiawan (Universitas Muhammadiyah Semarang, 2021)
This paper aims to analyze the transitivity of graduate students’ casual conversation. The conversation is transcribed then analyzed by using theory of transitivity. The research method applied Critical Discourse Analysis (CDA) which focused on transitivity analysis. Transitivity within the framework of Ideational Meaning was used as the theoretical framework for the analysis in this study. The analysis involved the analysis of processes and circumstances of the various clauses identified. The results revealed that the processes of material centrally concerned with actions and events of the speakers who carry them out, and the material processes also reveal the daily activity of speakers. Further, the circumstance of place is more dominant in this conversation.